The disciplined carnation - Ayala, José Luis (2019)
In the Tradition called The disciplined carnation, Ricardo Palma tells the story of the Viceroy Manuel de Amat y Junyent Planella Aymerich y Santa Pau and his servant Jaime, who was his confidant. Jaime knew all the secrets of the viceroy, especially the non-transparent way he made his great fortune. To be named Viceroy, one had to be supported by the King of Spain. The viceroy ordered to build a regal residence called “Quinta del Rincón” with his accumulated wealth, a building that could compete with some constructions in Madrid. The trial of residence against theviceroy De Amat lasted for a long time, he was blamed for real events, though some of them were unfair and imaginary. Later, he returned to Spain, filled with disgust. However, he gifted the “Quinta del Rincón” to his protégé Jaime.